A New Dated Inscription from the Reign of Horemheb - Redford, D. В. (1973)
16th year campaign from Byblos (Kpny) to Carchemish (Ḳrḳmš), cf. Mursilis II, Annals, year 7; Cf. Annual Egyptian Bibliography 1973, publ. 1977 173 (J. F. Borghouts).